2015
DOI: 10.1039/c5lc01025j
|View full text |Cite
|
Sign up to set email alerts
|

Kilo-scale droplet generation in three-dimensional monolithic elastomer device (3D MED)

Abstract: Droplet-based microfluidics has led to transformational new approaches in diverse areas including materials synthesis and high-throughput biological assays. However, the translation of droplet microfluidics technology into commercial applications requires scale-up of droplet generation from the laboratory (<10 mL h(-1)) to the industrial (>1 L h(-1)) scale. To address this challenge, we develop a three-dimensional monolithic elastomer device (3D MED) for mass production of monodisperse emulsion droplets. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 21 publications
2
116
0
Order By: Relevance
“…As described in our previous report, 26 we have developed a robust fabrication method for a three-dimensional monolithic elastomer device (3D MED) by eliminating the need for aligning and bonding multiple pieces of elastomer layers. A 3D MED with a three dimensional structure is fabricated by double-sided imprinting using a hard silicon master and a soft PDMS master.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in our previous report, 26 we have developed a robust fabrication method for a three-dimensional monolithic elastomer device (3D MED) by eliminating the need for aligning and bonding multiple pieces of elastomer layers. A 3D MED with a three dimensional structure is fabricated by double-sided imprinting using a hard silicon master and a soft PDMS master.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…By carefully designing the distribution network and tuning the channel resistances, it has been shown that up to 1,000 droplet generators can be integrated into a single microfluidic chip that has the production rate of several liters of liquid droplets per hour. 26 …”
Section: Introductionmentioning
confidence: 99%
“…(B) Through-hole-containing manifolds enable parallelization of a conventional droplet generation mode for unparalleled scales of production. Adapted from Jeong, H.-H.; Yelleswarapu, V. R.; Yadavali, S.; Issadore, D.; Lee, D. Lab Chip 2015 , Advance Article, DOI: 10.1039/C5LC01025J (ref 9) with permission of The Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%
“…However, coupled inlet and outlet flow paths present significant challenges to maintaining size control and low polydispersity of droplet diameter, due to propagation of pressure fluctuations between nozzles. Nonetheless, uniform droplet production has been shown on parallel droplet generators with a variety of configurations [30][31][32][33][34] . Parallel microfluidics have been used to produce microgels through light-initiated free-radical polymerization on single layer microfluidics, and the nature of crosstalk between parallel droplet generators has been studied in this context 35 .…”
Section: Introductionmentioning
confidence: 99%